Navigating Land Conflicts: Indigenous Rights in the Shadow of Ibu Kota Nusantara - Holy Regina Hartanto; Ariesta Bramantyo Syatya Putra; Rabbayani Daniswara; Nailah Fiorenza Fitriyah (Jurnal Penataan Ruang, 2025)
The development of the new capital city, Ibu Kota Nusantara (IKN) presents an example of how land use changes and concessions for land spark conflicts between agencies that obtained concessions and indigenous communities who claimed the land as theirs. Due to the land acquisition process, local communities have voiced concerns over the lack of transparency, consultation, and formal recognition of their land rights. The existing control mechanisms are still deemed weak. Thus, this research aimed to analyze the existing control mechanisms and formulate recommendations to improve them. To achieve this, policy review and case study approaches were used. The analysis showed that there's limited legal recognition and protection, prioritization of national strategic projects, and inadequate compensation procedures in our existing framework. The case study result showed that legal victories and court judgments can affirm indigenous land rights, even though their practical implementation often faces delays and resistance. State prioritizations on developments is also a growing trend among many states. Those results identified three main problems: the absence of legal recognition for indigenous people and their ancestral lands, insufficient regulation of land acquisition planning concerning national strategic projects, the calculation and form of compensation. Incentives, zoning regulations, permitting system, and enforcement monitoring system in land acquisition procedures were recommended. These systems are hoped to be able to improve the control mechanisms of development in indigenous lands.